Nuclearity expansion in Pd clusters triggered by the migration of a phenyl group in cyclooligosilanes. Issue 62 (13th July 2021) - Shimamoto, Kento; Sunada, Yusuke
Abstract : Heptanuclear palladium clusters were synthesized via the reaction of [Pd(CN t Bu)2 ]3 with Ph-substituted cyclooligosilanes. The generation of the SiPh moiety upon migration of a Ph group is the key to assembling the seven palladium atoms effectively. Abstract : Heptanuclear palladium clusters with six palladium atoms in a planar arrangement were obtained from the reaction of [Pd(CN t Bu)2 ]3 with Ph-substituted cyclotetrasilane or cyclopentasilane via the migration of a phenyl group. The molecular structures of these clusters as well as those of two possible intermediates were determined by single-crystal X-ray diffraction analyses.